2019
DOI: 10.1101/791038
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influenza B viruses exhibit lower within-host diversity than influenza A viruses in human hosts

Abstract: Influenza B virus undergoes seasonal antigenic drift more slowly than influenza A, but the reasons for this difference are unclear. While the evolutionary dynamics of influenza viruses play out globally, they are fundamentally driven by mutation, reassortment, drift, and selection within individual hosts. These processes have recently been described for influenza A virus, but little is known about the evolutionary dynamics of influenza B virus (IBV) at the level of individual infections and transmission events… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 47 publications
(60 reference statements)
0
21
0
Order By: Relevance
“…In the context of transmission between hosts, however, the potential for multiple infection may be limited. Indeed, the tight genetic bottleneck observed in human–human transmission is consistent with infection initiated by single particles 35 , 36 . In line with this concept, our prior work in a guinea pig transmission model revealed that a seasonal IAV engineered to be fully reliant on multiple infection replicated efficiently but did not transmit to contacts 34 .…”
Section: Discussionmentioning
confidence: 63%
“…In the context of transmission between hosts, however, the potential for multiple infection may be limited. Indeed, the tight genetic bottleneck observed in human–human transmission is consistent with infection initiated by single particles 35 , 36 . In line with this concept, our prior work in a guinea pig transmission model revealed that a seasonal IAV engineered to be fully reliant on multiple infection replicated efficiently but did not transmit to contacts 34 .…”
Section: Discussionmentioning
confidence: 63%
“…The rapidity of the evolutionary process that seemingly characterizes all RNA viruses ensures that genetic and phenotypic variation is generated and accumulates within individual hosts infected with influenza virus, although human influenza B virus may exhibit less intrahost diversity than influenza A virus (Valesano et al 2019). There is, however, considerable uncertainty as to how influenza virus evolves over such short timescales, and what this means for the long-term evolution of the virus (Xue et al 2018b).…”
Section: Intrahost Evolution Of Influenza Virusmentioning
confidence: 99%
“…Surprisingly, new antigenic variants are rarely observed in human seasonal influenza virus infections, even in recently infected or vaccinated hosts (Debbink et al, 2017; Dinis et al, 2016; McCrone et al, 2018; Leonard et al, 2016; Han, Maurer-Stroh, & Russell, 2019; Valesano et al, 2019) (Fig. 1A,B).…”
Section: Introductionmentioning
confidence: 99%